ANALISIS KEPUASAN KONSUMEN MENGGUNAKAN MODEL KANO (KASUS PADA LEMBAGA BIMBINGAN BELAJAR SMART GANESHA CABANG PANAM PEKANBARU) - Sembiring, Alfiusta; Zuliarni, Sri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The research was conducted at the Institute of Ganesha Smart TutoringBranch Panam Pekanbaru with the aim to analyze customer satisfaction in LBBGanesha Smart Panam Pekanbaru branch using a model canoe. Variable in thisresearch are: consumer satisfaction. The sample in this study are as many as 51customers using proportional random sampling technique. The analytical methodused is the Kano model analysis. The result showed that the model of Kano is theright model to improve customer satisfaction in LBB Ganesha Smart Cab. Panam,Pekanbaru. It can be seen from the attractive category that material submitted byLBB Tentor Smart Ganesha completed at each meeting as well as smart LBBGanesha has a teaching force which controls the material well, students in LBBsmart ganesha can improve self-esteem or pride in their students and follow theprogram the LBB Smart Ganesha can improve student achievement. grade mut besmart LBB Ganesha is no registration fee (registration geratis) and smart LBBGanesha provide WIFI geratis. Category One Dimensional namely educationcosts are relatively inexpensive and can be repaid. Ie indifferent category ofproducts in LBB Smart Ganesha in accordance with what is required of studentsand have a forte, the completeness of the products / services offered.Keywords: Consumer Satisfaction